Smallholder farmers' willingness to pay for agricultural production cost insurance in rural West Java, Indonesia: A contingent valuation method (CVM) approach - Mutaqin, Dadang Jainal; Usami, Koichi (Risks (Basel), 2019)
To reduce the negative impacts of risks in farming due to climate change, the government implemented agricultural production cost insurance in 2015. Although a huge amount of subsidy has been allocated by the government (80 percent of the premium), farmers' participation rate is still low (23 percent of the target in 2016). In order to solve the issue, it is indispensable to identify farmers' willingness to pay (WTP) for and determinants of their participation in agricultural production cost insurance. Based on a field survey of 240 smallholder farmers in the Garut District, West Java Province in August-October 2017 and February 2018, the contingent valuation method (CVM) estimated that farmers' mean willingness to pay (WTP) was Rp 30,358/ha/cropping season ($2.25/ha/cropping season), which was 16 percent lower than the current premium (Rp 36,000/ha/cropping season = $2.67/ha/cropping season). Farmers who participated in agricultural production cost insurance shared some characteristics: operating larger farmland, more contact with agricultural extension service, lower expected production for the next cropping season, and a downstream area location.